Conviction [videorecording (DVD)] - Goldwyn, Tony; Goldwyn, Tony; Swank, Hilary; Leo, Melissa; Rockwell, Sam; Driver, Minnie; Gallagher, Peter, 1955-; Lewis, Juliette (Twentieth Century Fox Home Entertainment, 2011)
Betty Anne Waters is a young woman whose world is shattered when her beloved brother Kenny is convicted of murder and sentenced to life in prison. Steadfastly convinced of his innocence, Betty Anne embarks on an 18-year journey to set Kenny free, using state-of-the-art forensic technology. The unshakable bond between a brother and sister, at the heart of this real-life drama, will stir your emotions and inspire you. Bonus features included.